2022
DOI: 10.1021/acs.joc.2c02345
|View full text |Cite
|
Sign up to set email alerts
|

From Induced-Fit Assemblies to Ternary Inclusion Complexes with Fullerenes in Corannulene-Based Molecular Tweezers

Abstract: The participation of the tether moiety in fullerene recognition of corannulene-based molecular tweezers is known to be an important factor. In the present work, we describe the synthesis of a set of fullerene receptors bearing two corannulene units located at a suitable distance to effectively interact with C 60 and C 70 . The tether comprises a fluorene-like scaffold where an assortment of different groups with variable electronic properties has been grafted. The photophysical and electrochemical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 86 publications
(194 reference statements)
1
5
0
Order By: Relevance
“…This resulted in binding constants of K a =(1.08±0.01)×10 3 M −1 for C 70 and K a =(1.50±0.1)×10 2 M −1 for C 60 . The obtained binding values are comparable to similar corannulene‐based receptors [8,10–12] . For ITC measurements, a corannulene receptor has been reported that reaches the same order of magnitude for the binding interactions with C 70 as our buckybowl catcher (literature value: K a = (2.0±0.1)×10 2 M −1 in o ‐DCB) [10] .…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…This resulted in binding constants of K a =(1.08±0.01)×10 3 M −1 for C 70 and K a =(1.50±0.1)×10 2 M −1 for C 60 . The obtained binding values are comparable to similar corannulene‐based receptors [8,10–12] . For ITC measurements, a corannulene receptor has been reported that reaches the same order of magnitude for the binding interactions with C 70 as our buckybowl catcher (literature value: K a = (2.0±0.1)×10 2 M −1 in o ‐DCB) [10] .…”
Section: Resultssupporting
confidence: 78%
“…The obtained binding values are comparable to similar corannulene-based receptors. [8,[10][11][12] For ITC measurements, a corannulene receptor has been reported that reaches the same order of magnitude for the binding interactions with C 70 as our buckybowl catcher (literature value: K a = (2.0 � 0.1)×10 2 M À 1 in o-DCB). [10] For NMR titrations, to the best of our knowledge no values are reported that have been measured in o-DCB.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Most remarkably, cavitand 1 provides K a 's in the 10 3 –10 4 M −1 range in a highly competitive solvent ( o -DCB), whereas previously reported hosts based on a single calix[5]arene macrocycle display K a 's in the 10 2 –10 3 range under similar conditions. 18 Constants in the range of those obtained for 1 can be replicated with receptors that feature multiple covalently tethered calix[5]arene 18,19 or corannulene recognition units, 31–33 but such hosts are much more challenging to synthesize and present limited diversification potential. For completeness, we also attempted fitting all our titration data to a 2 : 1 model given existing precedents, 17 resulting in a poor fit in all cases.…”
mentioning
confidence: 99%